Evaluation of Neurological Deficit in Hospital Discharged Encephalitis - Lubuk P. Saing; Robert MJ. Simanjutak; Manihar D. Marbun; Iskandar Z. Lubis; Bistok Saing (Paediatrica Indonesiana, 1996)
A study was done on 30 encephalistis patients treated and discharged from Dr. Pimgadi Hospital Medan in the year 1990-1991, The study was conducted cross sec- tionally. The aim of the study was to find out the type and percentage of neurological deficits, including factors associated with the sequelae. Eight patients (27%) developed neurological deficit, only (3%) patient developed neurological deficits after being disÂcharged until the period of evaluation. The neurological deficits encountered mostly were epilepsy, paraparesis, and right hemiparesis, each of which in 2 cases (7%), and monoÂparesis of the right limb and aphasia, each in 1 case (3%). The was no significant assoÂciation of neurological deficit with prognostic factor.